Endogenous Information Acquisition in Coordination Games. - Myatt, D; Wallace, C (Department of Economics (University of Oxford), 2010)
In the context of a “beauty contest” coordination game (in which payoffs depend on the quadratic distance of actions from an unobserved state variable and from the average action) players choose how much costly attention to pay to various informative signals. Each signal has an underlying accuracy (how precisely it identifies the state) and a clarity (how easy it is to understand). The unique linear equilibrium has interesting properties: the signals which receive attention are the clearest available, even if they have poor underlying accuracy; the number of signals observed falls as the complementarity of players’ actions rises; and, if actions are more complementary, the information endogenously acquired in equilibrium is more public in nature. The consequences of “rational inattention” constraints on information transmission and processing are also studied.